Acquisition and expression of conditioned taste aversion differentially affects extracellular signal regulated kinase and glutamate receptor phosphorylation in rat prefrontal cortex and nucleus accumbens - Marotta, Roberto; Fenu, Sandro; Scheggi, Simona; Vinci, Stefania; Rosas, Michela; Falqui, Andrea; Gambarana, Carla; De Montis, M. Graziella; Acquas, Elio (Frontiers in Behavioral Neuroscience, 2014)
Conditioned taste aversion (CTA) can be applied to study associative learning and its relevant underpinning molecular mechanisms in discrete brain regions. The present study examined, by immunohistochemistry and immunocytochemistry, the effects of acquisition and expression of lithium-induced CTA on activated Extracellular signal Regulated Kinase (p-ERK) in the prefrontal cortex (PFCx) and nucleus accumbens (Acb) of male Sprague-Dawley rats. The study also examined, by immunoblotting, whether acquisition and expression of lithium-induced CTA resulted in modified levels of phosphorylation of glutamate receptor subunits (NR1 and GluR1) and Thr34- and Thr75-Dopamine-and-cAMP-Regulated PhosphoProtein (DARPP-32). CTA acquisition was associated with an increase of p-ERK-positive neurons and phosphorylated NR1 receptor subunit (p-NR1) in the PFCx, whereas p-GluR1, p-Thr34- and p-Thr75-DARPP-32 levels were not changed in this brain region. CTA expression increased the number of p-ERK-positive neurons in the shell (AcbSh) and core (AcbC) but left unmodified p-NR1, p-GluR1, p-Thr34- and p-Thr75-DARPP-32 levels. Furthermore, post-embedding immunogold quantitative analysis in AcbSh revealed that CTA expression significantly increased nuclear p-ERK immunostaining as well as p-ERK-labeled axo-spinous contacts. Overall, these results indicate that ERK and NR1, but not GluR1 and DARPP-32, are differentially phosphorylated as a consequence of acquisition and expression of aversive associative learning. Moreover, these results confirm that CTA represents an useful approach to study the molecular basis of associative learning in rats and suggest the involvement of ERK cascade in learning-associated synaptic plasticity.